HyTES Campaign Calibration Data, Facility Instrument Collection - Hook, S.J.; Hulley, G.C.; La, T.T.; Rivera, G.; Johnson, W.R.; Eng, B.T. (ORNL Distributed Active Archive Center, 2026)
This dataset contains calibration data for the Hyperspectral Thermal Emission Spectrometer (HyTES) instrument. Calibration information is provided as a series of graphics saved in Portable Document Format (PDF). These graphics depict instrument responses to hot and cold black body targets by pixel and band as well as spectral response statistics. The NASA HyTES is an airborne imaging spectrometer with 256 spectral channels between 7.5 and 12 micrometers in the thermal infrared part of the electromagnetic spectrum and 512 pixels cross-track. HyTES has been deployed on DHC-6 Twin Otter, NASA's Earth Resources ER-2, and GulfStream V aircraft and completed its first flights in July 2012. HyTES was designed to provide high spectral and spatial resolution thermal infrared (TIR) data as a precursor for NASA's planned Hyperspectral Infrared Imager (HyspIRI) orbital mission. It is useful for a number of applications, including high-resolution surface temperature and emissivity measurements, point sources of air pollution, and volcano observations. NASA facility instruments operate out of a NASA research center and support multiple science disciplines, field investigations, and NASA science objectives. Facility instruments are supported by managers in the Earth Science Division (ESD) Research and Analysis Program, and/or the Earth Observation System (EOS) Project Science Office.
Keywords: SPECTRAL/ENGINEERING, SENSOR CHARACTERISTICS; SPECTRAL/ENGINEERING, PLATFORM CHARACTERISTICS, CALIBRATION; NASA ER-2, HyTES; NOAA Twin Otter, HyTES; G-V, HyTES; airborne instruments; NASA facility instruments; HyTES; spectral response; calibration